Mediasi Keunggulan Bersaing : Pengaruh Supply Chain Management terhadap Kinerja Perusahaan: Studi Kasus pada Pelaku Usaha Jasa Titip Gacoan - Muhammad Zakky Rosaely; Moh. Mukhsin; Enok Nurhayati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research seeks to examine, evaluate, and confirm how supply chain management impacts company performance, using competitive advantage as a mediating factor, focusing on gacoan noodle consignment service providers who apply official gacoan noodle supply chain management practices. A quantitative research method is utilized, collecting data through participatory observations, literature reviews, and surveys with questionnaires distributed to gacoan noodle consignment service providers. The study's participants are a micro-enterprise engaged in delivery services related to the retail distribution of gacoan noodle consignment services, comprising 45 individuals. A saturated sampling method was employed, meaning all 45 respondents were included in the study. Structural Equation Modeling (SEM) analysis was conducted with the SmartPLS 4 tool for data analysis. The findings of this research reveal: (1) Supply Chain Management positively and significantly influences Company Performance, where supply chain management's role in enhancing company performance is moderate, (2) Supply Chain Management positively and significantly impacts Competitive Advantage, with a notable large effect of supply chain management on competitive advantage, (3) Competitive Advantage positively and significantly affects Company Performance, where competitive advantage's role in improving company performance is moderate, and (4) Supply Chain Management positively and significantly affects Company Performance through Competitive Advantage as a mediator, revealing that the competitive advantage serves as a medium-level mediation between supply chain management and company performance.